RANCANGAN PENGOLAHAN DATA ASET DESA: VILLAGE ASSETS, DATA PROCESSING, INFORMATION SYSTEMS, WEB - Adhiatma, Novri; Sany, Ezrifal; Ikhsan, Muhammad (LP2M STMIK Nurdin Hamzah Jambi, 2018)
An information system is very necessary in improving the performance of an organization, be it a private or government organization. The government in data processing still uses standard application programs that are widely used such as Microsoft Excel and Microsoft Word in the processing of village asset data so that data processing and data search processes become less effective. Therefore, it is necessary to develop a system that is used today by using an information system specifically designed for processing village asset data so that data processing and data search processes become more effective. The village asset data processing information system is built using web-based programming languages such as PHP and MySQL databases. Web-based programming languages have excellent capabilities in processing text, graphics, numbers and databases. With the construction of an information system, data processing of village assets can help the processing of village asset data at the Village Office become easier and more effective.